2017
DOI: 10.1089/dia.2016.0423
|View full text |Cite
|
Sign up to set email alerts
|

A Pediatric Intensive Care Unit Bedside Computer Clinical Decision Support Protocol for Hyperglycemia Is Feasible, Safe and Offers Advantages

Abstract: Background: Computer clinical decision support (CDS) systems are uncommon in the pediatric intensive care unit (PICU), despite evidence suggesting they improve outcomes in adult ICUs. We reasoned that a bedside CDS protocol for intravenous insulin titration, eProtocol-insulin, would be feasible and safe in critically ill children. Methods: We retrospectively reviewed data from non-diabetic children admitted to the PICU with blood glucose (BG) ‡140 mg/dL who were managed with intravenous insulin by either unaid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…This clinical decision support tool has the potential to deliver relevant higher-order information on patient stability. When incorporated into a robust clinical decision support protocol, ID o 2 may be able to inform earlier weaning decisions and therefore improve on the accuracy and efficiency of care de-escalation ( 12 , 13 , 21 , 23 , 24 ). Future studies should aim to assess the clinical relevance of risk analytic algorithms during the de-escalation phases of care.…”
Section: Discussionmentioning
confidence: 99%
“…This clinical decision support tool has the potential to deliver relevant higher-order information on patient stability. When incorporated into a robust clinical decision support protocol, ID o 2 may be able to inform earlier weaning decisions and therefore improve on the accuracy and efficiency of care de-escalation ( 12 , 13 , 21 , 23 , 24 ). Future studies should aim to assess the clinical relevance of risk analytic algorithms during the de-escalation phases of care.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Additionally, the use of CDS systems for multicenter research trials are often underutilized. 2 , 3 , 4 With the use of an electronic CDS system, Children’s Hospital Euglycemia for Kids Spreadsheet (CHECKS), the National Institutes of Health-funded Heart and Lung Failure-Pediatric Insulin Titration (HALF-PINT) trial demonstrated that blood glucose control to a target of 80 to 110 mg/dL with IV insulin was associated with increased hypoglycemia and conferred no advantage compared with a blood glucose target of 150 to 180 mg/dL. 5 Large multicenter trials provide the highest quality evidence that indicates the optimal approach to blood glucose control with IV insulin.…”
mentioning
confidence: 99%